Cross-reactivity of HIV vaccine responses and the microbiome. Issue 1 (January 2018) - Williams, Wilton B.; Han, Qifeng; Haynes, Barton F.
Abstract : Purpose of review: A successful human immunodeficiency virus-type 1 (HIV-1) vaccine will require immunogens that induce protective immune responses. However, recent studies suggest that the response to HIV-1 and perhaps other viruses may be altered by immune system exposure to intestinal microbiota-antigens. This review will discuss select aspects of these studies. Recent findings: Naïve CD4 T and B cell repertoires can be imprinted by intestinal microbiota-antigens to respond to virus epitopes prior to virus infection. A multiclade envelope (Env) gp145 DNA prime, recombinant adenovirus type 5 boost vaccine tested in a HIV Vaccine Trials Network (HVTN) phase IIb human vaccine efficacy trial (HVTN 505) induced a dominant gp41-reactive antibody response that was non-neutralizing and cross-reactive with intestinal microbiota. This vaccine regimen also induced a dominant gp41-reactive, intestinal microbiota-cross-reactive gp41 antibody response in neonatal and adult Rhesus macaques. Studies of naïve CD4 T cells have demonstrated cross-reactivity to both HIV-1 and influenza peptides. Summary: HIV-1 Env vaccine-induced CD4 T and B cell responses can originate from a pool of intestinal microbiota-cross-reactive immune cells. Moreover, intestinal microbiota-cross-reactive HIV-1 Env antibodies are ineffective in protection against HIV-1 infection. Thus, intestinal microbiota-imprinting of the B cell repertoire may be one of several roadblocks to the induction of protective HIV-1 antibodies.